Evaluating the evidence for ecological effectiveness of South Africa's marine protected areas. Issue 3 (3rd July 2021) - Kirkman, SP; Mann, BQ; Sink, KJ; Adams, R; Livingstone, T-C; Mann-Lang, JB; Pfaff, MC; Samaai, T; van der Bank, MG; Williams, L; Branch, GM
Abstract : We reviewed 140 papers to assess the ecological effectiveness of South Africa's marine protected areas (MPAs). Evidence was assessed for coverage and representivity, protection of important biodiversity areas, other recognised elements of effectiveness, connectivity, and ecological effects—from the scale of individual MPAs to the MPA network scale. We conducted complementary novel analyses to supplement the review and to objectively determine where and how the MPA network can be improved. Evidence shows that South Africa's MPAs now provide some protection to all ecoregions and 87% of ecosystem types but to less than 50% of assessed species groups. MPAs are generally well-sited, but gaps were revealed on the west coast and in estuaries, the deep sea, and two ecologically and biologically significant areas. Enforcement emerged as a key concern, and many MPAs could be improved through expansion or by increasing no-take areas. The majority of relevant papers recorded beneficial ecological effects, detectable as increases in parameters such as the abundance, biomass, sizes or reproductive output of species. Few papers examined whether ecological benefits translate into adjacent fisheries benefits, but all those that did recorded positive effects. Full protection was more effective than partial protection, with effectiveness most clearly demonstrated for vulnerable target taxa. Further research and monitoring to achieve evaluations of effectiveness are recommended, with greater focus on neglected MPAs and species. Understanding the ecological connectivity between MPAs, an important dimension for climate-change adaptation and hence for the persistence and resilience of South Africa's marine biodiversity, is identified as a key area for future research and inclusion in MPA planning.